A new family of scorpionflies (Insecta; Mecoptera) from the Lower Cretaceous of England. (July 2016) - Novokshonov, Victor G.; Ross, Andrew J.; Cook, Elizabeth; Krzemiński, Wiesław; Soszyńska-Maj, Agnieszka
Abstract: Seven specimens of fossil scorpionflies (Mecoptera) not assignable to any known family were discovered in the Wealden Supergroup (Lower Cretaceous) of southern England. They were found at Rudgwick Brickworks, West Sussex and Smokejacks Brickworks, Surrey and came from the Upper Weald Clay Formation, dated as Barremian (∼129.4–125 Ma). A new family – Englathaumatidae fam. nov., new genus – Englathauma gen. nov. and two new species E. crabbi sp. nov. and E. mellishae sp. nov. are described. A discussion of systematic position of these new taxa within the order Mecoptera is given. Englathaumatidae fam. nov. has been a nomen nudum since the year 2002, due to the first author's untimely death.